Unravelling the Influence of Nutrition and Mental Stress on Immune Response - Mishra, Rashmi; Pandey, Pratibha; Khan, Fahad (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
The review article reveals the role of mental as well as biological phenomena working behind immunity. In recent times, irresistible illnesses and inflammation have been thought to be hereditary or the result of the natural working mechanism of the human body in response to the pathogenic variables working inside the human system. In the past few years, the importance of psychological adjustments, mental well-being and eating habits has been studied and shown to have a marked effect on immunity. Psychoneuroimmunology considers that mental disorders are strongly interrelated with the resistant reaction. Besides, the immunological components control the wellbeing of the individual. Psychosocial mediations help reduce disease severity and enhance the functioning of the immune system. Nutrition plays a vital role in immunity and thus has an influence on our mental health.
Keywords: nutrition